Program Edukasi 1000 HPK (Hari Pertama Kehidupan) Terhadap Ibu Hamil Dan Keluarga Di Desa Penfui Timur Kabupaten Kupang - Muhammad Husain Hasan; Bella Theo Tomi Pamungkas; Arfita Rahmawati (Jurnal Kelimutu Pengabdian Masyarakat, 2022)
The high rate of stunting in East Nusa Tenggara Province must be done by preventing stunting or failure to grow from the first 1000 days of a child's life. Adequate food intake for pregnant women so that the fetus develops properly. If the mother's food intake is sufficient and there are no other complications, generally the fetus will grow and develop well. Adequacy of this food intake can later be seen by the weight gain of the fetus by gestational age. Respondents in this study were pregnant women and their families who are members of the Rindu Sejahtera Posyandu community, East Penfui Village, Kupang Regency. The data collection technique used pre-test and post-test questionnaires. Analysis of the data using the formula Percentage Score (PS) = total score acquisition (n) / total score maximum (N). The results showed that before the education was conducted, the average score obtained by the respondents was 70.59%, while the average score after the educational activities was 82.35%. The educational materials after interviewing the participants showed that all participants had never received socialization about the first 1000 days of life.